Cyclin K dependent regulation of Aurora B affects apoptosis and proliferation by induction of mitotic catastrophe in prostate cancer. Issue 8 (12th July 2017) - Schecher, Sabrina; Walter, Britta; Falkenstein, Michael; Macher‐Goeppinger, Stephan; Stenzel, Philipp; Krümpelmann, Kristina; Hadaschik, Boris; Perner, Sven; Kristiansen, Glen; Duensing, Stefan; Roth, Wilfried; Tagscherer, Katrin E.
Abstract : Cyclin K plays a critical role in transcriptional regulation as well as cell development. However, the role of Cyclin K in prostate cancer is unknown. Here, we describe the impact of Cyclin K on prostate cancer cells and examine the clinical relevance of Cyclin K as a biomarker for patients with prostate cancer. We show that Cyclin K depletion in prostate cancer cells induces apoptosis and inhibits proliferation accompanied by an accumulation of cells in the G2/M phase. Moreover, knockdown of Cyclin K causes mitotic catastrophe displayed by multinucleation and spindle multipolarity. Furthermore, we demonstrate a Cyclin K dependent regulation of the mitotic kinase Aurora B and provide evidence for an Aurora B dependent induction of mitotic catastrophe. In addition, we show that Cyclin K expression is associated with poor biochemical recurrence‐free survival in patients with prostate cancer treated with an adjuvant therapy. In conclusion, targeting Cyclin K represents a novel, promising anti‐cancer strategy to induce cell cycle arrest and apoptotic cell death through induction of mitotic catastrophe in prostate cancer cells. Moreover, our results indicate that Cyclin K is a putative predictive biomarker for clinical outcome and therapy response for patients with prostate cancer. Abstract : What's new? Cell cycle progression genes represent a promising source for biomarker discovery in prostate cancer, though little is known about their role in the disease. This study shows in prostate cancer cells that depletion of Cyclin K, a cell cycle regulator, is associated with apoptosis and inhibition of proliferation. The effects of Cyclin K downregulation were linked to Cyclin K dependent and Aurora B‐mediated induction of mitotic catastrophe. In patients treated with adjuvant therapy, Cyclin K expression was associated with reduced biochemical recurrence‐free survival. The results warrant further investigation of Cyclin K as predictive biomarker in prostate cancer.